Anak Didik Dalam Pendidikan Islam - Saifuddin Saifuddin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2013)
The purpose of this study was to determine how students position in Islam and how to view a few theories about human potential and how the concept of nature as a potential base. This type of research is literature. Based on the results of studies which have shown that education as a business builder and personal development of human physical and spiritual aspects, and therefore the development of new growth can be achieved when underway towards the ultimate goal of development and growth. There are multiple streams or theories in education related to the likelihood or traits among the students in the flow of nativism which assumes that human development has been determined by factors under human from birth. empiricism flow states depending on the child's development environment, while the carriage is not important: because at the time of birth of a child is still clean, and assume that the flow convergence pambawaan and environment are equally important and have the same effect . Islam considers that the human being is sacred hakeketnya which carries a potential base in the know with nature, so that the educational process must be aligned on the basis of the pattern of nature that has been in the form of God in every human person